(3VjYI GdYbO Ydi aJhi MGL SjO eMeO HGbQ GdTjYis
(3ChdgG (B:s
(3SDGd CfcMJ ehcdJi ehcdc Ydi GdUOGb s
(3BNQgG (B:s
(3GdMeO ddg GdPi CMd GdfcGM hGdJfRhjL ddCfGe hMQe GdRfG hGdSaGM JeJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI eOjfI GdYde (B_ (3GdcGXejI (B(278) s
Keywords: (3GdJhMjO hGdedd hGdfMds